Performance analysis of a MC-OFDM DS-CDMA system over a faded channel - Sarwar, Jakia; Nujhat, Tanziha (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.